Together forever? How customer co-creation affects the adoption of digital service innovations over time - Sven Heidenreich; Slawka Jordanow; Tobias Kraemer; Martin Obschonka (Journal of Product Innovation Management, 2024)
This study delves into the intricate relationship between customers' willingness to co-create (WCC) and the required level of co-creation (LCC) for effective service innovation adoption. In response to recent findings suggesting a "co-creation sweet spot," beyond which additional co-creation activities have detrimental effects, this research aims to provide both theoretical and empirical insights into this phenomenon. Unlike previous investigations focusing on either the willingness to co-create or the level of co-creation at a particular point in time and overlooking potential interactions, our study considers their interactions over time, acknowledging that revenue for most digital services is generated through ongoing customer usage. Utilizing longitudinal data from 352 participants across four waves and employing structural equation modeling, our analysis reveals a nuanced pattern. Customers' willingness to co-create predominantly shapes usage intention in the pre-adoption stage, while the level of co-creation becomes a critical driver for continuous usage in the post-adoption stages. Further analysis using response surface analysis with polynomial regression confirms a specific matching logic: customers with low (high) willingness to co-create expect a low (high) level of co-creation from a service innovation. From a theoretical perspective, our findings contribute to bridging the research gap concerning an optimal co-creation level, offering insights into psychological processes underlying the co-creation sweet spot. Furthermore, we also shed light on temporal aspects of the interplay between willingness to co-create and the level of co-creation, offering a more holistic perspective on their joint influence on adoption behavior. From a managerial perspective, our study challenges the traditional assumption that more co-creation naturally leads to better outcomes. It emphasizes the significance of tailoring the level of co-creation in digital service innovations based on customers' intrinsic willingness. This strategic customization aligns with the evolving landscape of digital service innovation, offering practical insights for managers striving to optimize their co-creation strategies.
Keywords: 650; adoption; co-creation; continuous usage; digital services; innovation